(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the quality of residual blood in extracorporeal circulation circuits, through a literature review. Methodology: This is a literature review on the reuse of residual blood from patients in the perioperative period of cardiac surgery with cardiopulmonary bypass. Consisting of the construction of a broad analysis of the literature, articles were collected in the PUBMED, SCIELO and GOOGLE ACADÊMICO databases using the descriptors in English and Portuguese, such as cardiopulmonary bypass, residual blood, cardiac surgery, Cell saver. Cardiac Surgery. Extracorporeal Circulation. Cell saver. Articles published in the years 2010 to 2020 will be searched. Results: According to the studies presented, the reuse of residual blood in cardiac surgeries accompanied by CPB reduced the need and quantity of allogeneic red blood cell transfusions, there was a significant improvement in hemoglobin levels, reduced blood loss in the postoperative period, decreased the use of stocked red cell concentrate and there was a higher rate of hemolysis. Conclusion: it is indispensable for an advance accompanied by multidisciplinary questions to better understand this blood and recovered cells, as well as the search for the best treatment for these patients and consequent improvement in the quality of life.